Brazil : Critical Issues in Social Security - World Bank (Washington, DC, 2013)
Social security is the single most important fiscal issue facing the Brazilian government today. This report summarizes the state, and potential policy implications, of the Brazilian Social security system. It also discusses policy recommendations for: social security and pensions, the national social security system, government pensions and funds, and the complementary pension systems. An overview of the social security challenge reviews the system components, revealing unsustainable fiscal imbalances and administrative weaknesses in both the unreformed General Regime for Social Security (RGPS), and the Pension Regime for Government Workers (RJU), with large tax-related distortions, and labor market inefficiency. Thus the goals of Brazil's reforms are to reduce fiscal deficits, lower actuarial imbalances, increase equity and redistribution, reduce collateral inefficiencies, and facilitate growth of funded pensions. The study implies there is no recourse for the country, but to lower the high, uniform replacement rates (experience suggests that rates higher than 40-70 percent, cannot be sustained). The key to effective reform of social security is widening the debate to include potential winners from these changes, particularly the private sector, the young, and the poor. Policy recommendations suggest that the adverse equity effects of RGPS reforms should be widely publicized to generate political support for deeper RJU reform.